A phosphonate–lanthanoid polyoxometalate coordination polymer: Ce2P2W16O60L2n zipper chains. Issue 35 (27th August 2021) - Wang, Wenyan; Izarova, Natalya V.; van Leusen, Jan; Kögerler, Paul
Abstract : The first coordination polymer of a polyoxometalate bi-functionalized by phosphonate and lanthanoid groups forms when {Ce III 2 (α2, -P V 2 W VI 16 O60 )L2 } units are joined by direct inter-cluster Ce–OW bonds into 1D chains. Abstract : {α2, -P2 W16 O60 } polyoxotungstate cluster units featuring phenylphosphonates and Ce III ions embedded into the segregated lacunary sites of the cluster shell organize into the first coordination polymer of a polyoxometalate functionalized by both organophosphonate and lanthanoid. Inter-cluster Ce–OW links result in double-chains, with {Ce III 2 (α2, -P V 2 W VI 16 O60 )L2 } cluster units oriented alternatingly perpendicular to the chain propagation direction, akin to the protruding teeth of a zipper.